Clustering Area to Reduce Stunting Rates in Central Java - Susanti, Desilia Wimbi; Tanur, Erwin; Sitanggang, Yuliana Ria Uli (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2023)
Accelerating the reduction of the stunting rate is the government's focus until the end of 2024. Efforts to reduce the stunting rate need to pay attention to the variable factors that cause stunting under five children and the characteristics of the region so that optimal results can be obtained. This study aims to grouping regencies based on the causes of stunting in toddlers in Central Java Province. This research expected make a contribution to the Central Java Government in determining policies related to reducing stunting rates that are more appropriate by taking into account regional characteristics. The research design uses descriptive analysis and cluster analysis. The grouping of regencies in Central Java Province using cluster analysis resulted in three clusters, namely clusters with low, medium, and high stunting factors. Regencies in the first cluster need increased access to proper sanitation, JKN ownership, and increased welfare. The second cluster needs to focus on increasing JKN ownership, while the third cluster needs to focus on increasing the coverage of exclusive breastfeeding and early breastfeeding.